Cohesion coefficient of structural concrete made with recycled concrete coarse aggregate. Issue 4 (8th July 2020) - Sahoo, Dipak Kumar; Mathew, Praveen
Abstract : Cohesion coefficient of structural concrete made with recycled concrete coarse aggregate (RCA) was evaluated independently for the first time through push-off tests having no clamping force across the shear plane and compared with the cohesion coefficient of structural concrete made with natural coarse aggregate (NCA). Both conventionally compacted and self-compacting concretes were made with RCA and NCA as coarse aggregates. To achieve the best structural quality, concretes made with RCA were proportioned based on the equivalent mortar volume (EMV) principle instead of percentage replacement of NCA with RCA commonly followed in most of the earlier studies. Twelve transversely unreinforced push-off specimens, three from each of the four varieties of concrete, were tested to failure. Cohesion coefficients determined from analytical and finite-element modelling of the push-off tests were found to be in close conformity with each other, and the experimentally found cohesion coefficients were reasonably close to, though not in exact conformity with, the theoretical values. Nevertheless, the experimental results clearly established that RCA concrete when proportioned by the EMV method is not inferior to NCA concrete in terms of cohesion contribution to shear strength.